2017
DOI: 10.7307/ptt.v29i3.2133
|View full text |Cite
|
Sign up to set email alerts
|

A Key Station Identification Method for Urban Rail Transit: A Case Study of Beijing Subway

Abstract: INTRODUCTIONWith the rapid development of urban rail transit network operation technique, the increase of passenger volume leads to congestion in stations [1], causing even safety risk in the network [2]. Besides, the topology of urban rail transit network can also aggravate or relief the congestion situation of subway networks. Therefore, an effective method identified the key station is an imperative to manage the overcrowded urban rail transit.For the factors of the station performance, many of the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Lai et al [36] established urban rail topology models of multiple cities, the toke network efficiency, and the largest connected subgraph as indicators to measure the network performance, and they found that the KSD identification method was superior to the node degree, neighbor node degree, DKS, and DKSN identification methods. Some scholars realized that there are differences in node importance in different application environments, and they tried to improve and even build new evaluation methods to more accurately obtain the key nodes that have the greatest impact on the urban rail network performance [37][38][39]. Liu et al [37] defined the topology of urban rail networks using the idea of Space P and Space L and a new parameter to evaluate the node importance and found that urban rail networks are more vulnerable to intentional attacks than random network attacks based on this node importance method.…”
Section: Evaluation Of Node Importance Of Urban Rail Networkmentioning
confidence: 99%
“…Lai et al [36] established urban rail topology models of multiple cities, the toke network efficiency, and the largest connected subgraph as indicators to measure the network performance, and they found that the KSD identification method was superior to the node degree, neighbor node degree, DKS, and DKSN identification methods. Some scholars realized that there are differences in node importance in different application environments, and they tried to improve and even build new evaluation methods to more accurately obtain the key nodes that have the greatest impact on the urban rail network performance [37][38][39]. Liu et al [37] defined the topology of urban rail networks using the idea of Space P and Space L and a new parameter to evaluate the node importance and found that urban rail networks are more vulnerable to intentional attacks than random network attacks based on this node importance method.…”
Section: Evaluation Of Node Importance Of Urban Rail Networkmentioning
confidence: 99%
“…Moreover, some scholars have considered PFV (passenger flow volume) while exploring network features, as it reflected the transportation capacity of RTN. The importance ranking of RTN nodes has been determined based on the variance contribution of each indicator using techniques like Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) and factor analysis [ 33 , 34 ]. It has been pointed out that attacks based on the highest load node could result in more damages compared with the attacks based on the largest degree node [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of information technology, large amounts of data over time and space are available to model urban dynamics. In particular, monitoring, recognising and analysing human mobility patterns is becoming a hot issue in transport and urban planning [39][40]. Urban traffic arises from an interplay between the dynamics of the individual movements and its underlying structure.…”
Section: Introductionmentioning
confidence: 99%